Sakta ner : åtgärder för förbättrad miljö och trafiksäkerhet på gator i bostadsområden i Varberg, idékatalog och tillämpning - Anding, Julia (SLU/Dept. of Urban and Rural Development, 2008)
Road safety is the result of measures to reduce the risk of accident and injury. (Nationalencyklopedin, 2008). In principle, road safety means to arrive save and sound.